Implementasi Spiritualitas di Tempat Kerja untuk Meningkatkan Kinerja Karyawan di Sanctoo Suites & Villas - Pramana, Made Dwitya Teja; Astawa, I Ketut; Winia, I Nyoman; Sudiarta, Made; Suparta, I Ketut (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: The purpose of this study is to determine the implementation of spirituality in the workplace and the effect of the implementation to the performance of employees at Sanctoo Suites & Villas, Singapadu, Gianyar. Research methods: The type of data in this study is primary data which obtained through observation, interviews, and questionnaires from 60 samples. The data analysis technique used is simple linear regression and processed through the SPSS. Results and discussion: The management of Sanctoo Suites & Villa has not explicitly implemented spirituality in the workplace buat implicitly the concept of spirituality in the workplace has been applied by management based on three dimensions that build spirituality in the workplace, namely meaningful work, feeling connected to the community, and alignment with organizational values. Spirituality has a positive influence on employee performance at Sanctoo Suites & Villas. Implication: This study has particular implications for the Sanctoo Suites & Villa management in building value dimensions that can increase the spirituality of employees in carrying out their duties so that they can contribute to the performance of their employees and to the companies.